TLR4-mediated chronic neuroinflammation has no effect on tangle pathology in a tauopathy mouse model - Basheer, Neha; Muhammadi, Muhammad Khalid; Freites, Carlos Leandro; Avila, Martin; Momand, Miraj Ud Din; Hryntsova, Natalia; Smolek, Tomas; Katina, Stanislav; Zilka, Norbert (Frontiers in Aging Neuroscience, 2024)
Introduction Alzheimer’s disease (AD) is marked by the accumulation of fibrillary aggregates composed of pathological tau protein. Although neuroinflammation is frequently observed in conjunction with tau pathology, current preclinical evidence does not sufficiently establish a direct causal role in tau tangle formation. This study aimed to evaluate whether chronic Toll-like receptor 4 (TLR4) stimulation, induced by a high dose of lipopolysaccharide (LPS, 5 mg/kg), exacerbates neurofibrillary tangle (NFT) pathology in a transgenic mouse model of tauopathy that expresses human truncated 151-391/3R tau, an early feature of sporadic AD. Methods We utilized a transgenic mouse model of tauopathy subjected to chronic TLR4 stimulation via weekly intraperitoneal injections of LPS over nine consecutive weeks. Neurofibrillary tangle formation, microglial activation, and tau hyperphosphorylation in the brainstem and hippocampus were assessed through immunohistochemistry, immunofluorescence, and detailed morphometric analysis of microglia. Results Chronic LPS treatment led to a significant increase in the number of Iba-1+ microglia in the LPS-treated group compared to the sham group (p < 0.0001). Notably, there was a 1.5- to 1.7-fold increase in microglia per tangle-bearing neuron in the LPS-treated group. These microglia exhibited a reactive yet exhausted phenotype, characterized by a significant reduction in cell area (p < 0.0001) without significant changes in other morphometric parameters, such as perimeter, circumference, solidity, aspect ratio, or arborization degree. Despite extensive microglial activation, there was no observed reduction in tau hyperphosphorylation or a decrease in tangle formation in the brainstem, where pathology predominantly develops in this model. Discussion These findings suggest that chronic TLR4 stimulation in tau-transgenic mice results in significant microglial activation but does not influence tau tangle formation. This underscores the complexity of the relationship between neuroinflammation and tau pathology, indicating that additional mechanisms may be required for neuroinflammation to directly contribute to tau tangle formation.